1987
DOI: 10.1007/bf00113906
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of biogenic sulfur emissions from soils and vegetation: Application of dynamic enclosure methods with Natusch filter and GC/FPD analysis

Abstract: Abstract. Emission rates of reduced sulfur gases from vegetation and soils were measured in various regions of the United States during the summer of 1985. The predominant sulfur gases emitted were hydrogen sulfide, carbonyl sulfide and dimethylsulfide. Typically, vegetative (forests, crops, etc.) emission fluxes varied between approximately 10 and 60 ng S m -2 min -1 . Biogenic sulfur fluxes from mollisol and histisol soils averaged 15 and 217 ng S m -x min -I , respectively. Salt water marsh fluxes with a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 18 publications
6
63
0
Order By: Relevance
“…The increase in the MSA concentrations may have been due to either enhanced contributions of marine air masses advectively transported from the sea or the oxidation of terrestrial biogenic DMS (Lamb et al, 1987). In fact, emissions of sulfur gases (DMS, H 2 S, and CS 2 ) have been reported for plant canopies (deciduous trees and pines) (Andreae et al, 1990) and mollisol and histisol soil (Lamb et al, 1987). Fig.…”
Section: Possible Sources Of Msamentioning
confidence: 95%
“…The increase in the MSA concentrations may have been due to either enhanced contributions of marine air masses advectively transported from the sea or the oxidation of terrestrial biogenic DMS (Lamb et al, 1987). In fact, emissions of sulfur gases (DMS, H 2 S, and CS 2 ) have been reported for plant canopies (deciduous trees and pines) (Andreae et al, 1990) and mollisol and histisol soil (Lamb et al, 1987). Fig.…”
Section: Possible Sources Of Msamentioning
confidence: 95%
“…Subsequent studies have found that aromatic and alkane compounds appear to be a very minor component of total NMVOC emissions. In addition to the compounds included in Table 5, VOC that have been reported as vegetation emissions include alkanes (C to C ), alkenes (C to C ), ketones (pentanone, octanone, methyl heptanone), alcohols (methyl propanol, butanol, octanol), aldehydes (propanal, butanal and butenal), organic acids (pyruvic and propionic acid) and organic sulfur compounds (dimethyl sul"de, dimethyl disul"de, dipropenyldisul"de and methylpropenyldisul"de) (Isidorov et al, 1985;Lamb et al, 1987b;Talbot et al, 1990;Servant et al, 1991;Winer et al, 1992;Harbourne, 1993;Konig et al, 1995;Guenther et al, 1996b;Puxbaum and Konig, 1997). The pathways for biosynthesis of some of these compounds, e.g., pentane (Pattee et al, 1974) and heptane (Savage et al, 1996), have been described, but the processes leading to the emission of many of these compounds are unknown.…”
Section: Regional Landcover and Climate Changementioning
confidence: 99%
“…However, recently, field studies and laboratory simulations have presented convincing evidence that soils act more as a sink than as a source for COS (Castro and Galloway, 1991;Fried et al, 1993;de Mello and Hines, 1994;Kesselmeier et al, 1999;Kettle et al, 2002;Geng and Mu, 2004;Yi et al, 2007Yi et al, , 2008Van Diest and Kesselmeier, 2008). Earlier researchers investigating COS exchange usually used enclosure methods with COS-free sweep air (Aneja et al, 1979;Adams et al, 1981;Goldan et al, 1987;Lamb, et al, 1987;MacTaggart et al, 1987), which masked the potential of soils to act as a sink for sulfur compounds. In contrast, some other researchers used very high concentration of COS to study the potential of soils to take up COS (Bremner and Banwart, 1976;Kluczewski et al, 1985;Lehmann and Conrad, 1996), which also generated artificial COS concentration gradients.…”
Section: Introductionmentioning
confidence: 99%